2020
DOI: 10.2807/1560-7917.es.2020.25.32.2001410
|View full text |Cite|
|
Sign up to set email alerts
|

Geographical and temporal distribution of SARS-CoV-2 clades in the WHO European Region, January to June 2020

Abstract: Investigator group: The members of the WHO European Region sequencing laboratories and GISAID EpiCoV group are listed at the end of the article

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
230
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(254 citation statements)
references
References 12 publications
(12 reference statements)
16
230
0
2
Order By: Relevance
“…The discrepancy in the GR clade abundance between the set of 115 Polish sequences collected between March and mid-June, and the European reference sequences collected until April 9th was mostly due to the contribution of Polish sequences collected after April 9th; the frequency of Polish isolates collected until April 9th was much closer to that in the European dataset. Indeed, the recent study on the SARS-CoV-2 geographical and temporal distribution in Europe, encompassing the period from January to mid-June (Alm et al 2020 ), has indicated that the frequency of the GR clade in April was ~ 30%, consistent with our calculations based on the manual analysis of the GISAID data. However, early in June, the GR clade frequency in Europe overtook that of the other clades, and since then is on the constant rise.…”
Section: Discussionsupporting
confidence: 91%
“…The discrepancy in the GR clade abundance between the set of 115 Polish sequences collected between March and mid-June, and the European reference sequences collected until April 9th was mostly due to the contribution of Polish sequences collected after April 9th; the frequency of Polish isolates collected until April 9th was much closer to that in the European dataset. Indeed, the recent study on the SARS-CoV-2 geographical and temporal distribution in Europe, encompassing the period from January to mid-June (Alm et al 2020 ), has indicated that the frequency of the GR clade in April was ~ 30%, consistent with our calculations based on the manual analysis of the GISAID data. However, early in June, the GR clade frequency in Europe overtook that of the other clades, and since then is on the constant rise.…”
Section: Discussionsupporting
confidence: 91%
“…The first SARS-CoV-2 infected patient was identified in Poland on 4 th March 2020, and since then, the genetic drift of the virus was monitored. The phylogenetic analysis led to the conclusion that the diversity of the virus is similar to the one observed worldwide [ 6 ]. The virus was introduced to the population of Poland from different sources, as hallmarks of different clades are present; virtually all genetic clades identified thus far were present [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
“…We prepared libraries from these 4000 bp-long amplicons using Illumina TruSeq adapter sequences and sequenced them on an Illumina MiSeq System (Paired-end sequencing, 2x 251 cycle). The phylogenetic relationship between the consensus sequence of 681 samples from this collection has been previously analyzed as part of the subset of GISAID data available for Switzerland until July 10, 2020 in [24] and results based on the consensus sequences of the full dataset are presented in [45]. Here we focus on the raw reads directly and analyse the deep sequencing data to uncover within host diversity.…”
Section: Methodsmentioning
confidence: 99%
“…The sequences generated are largely deposited in data repositories such as the sequence read archive (SRA) and GISAID [19]. The availability of these sequences has allowed for platforms such as Nextstrain [20] to continually update and track viral evolution and spread, and to illuminate the viral genetic diversity among carriers [2124].…”
Section: Introductionmentioning
confidence: 99%